Pengaruh Persepsi Manfaat, Kemudahan, dan Kesesuaian Tugas‑Teknologi terhadap Minat dan Penggunaan Aktual Layanan Internet Nasabah BCA X - Durahman Durahman; Sigit Pamungkas (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study examines the factors influencing the intention to use KlikBCA Internet services at BCA Tegal branches and their subsequent impact on actual usage. The research utilized a random sample of 125 customers and employed path analysis to assess the relationships between key variables. The results indicate that perceived usefulness (contributing 27.15% of the influence) and perceived ease of use (8.51%) have a significant positive effect on the intention to use KlikBCA services. On the other hand, task-technology fit was found to have a negative effect on the intention to use the service. This suggests that the alignment between the user's task requirements and the technology offered by KlikBCA may not always contribute positively to the user's intention to adopt the service. Furthermore, the study reveals that perceived usefulness (9.02%) and intention to use (10.67%) both significantly and positively affect actual usage of the service. These findings highlight that, for increasing customer adoption and usage, it is crucial for BCA to emphasize the perceived benefits and ease of use of digital banking services. The positive impact of perceived usefulness reinforces the importance of ensuring that customers see real value in using online banking services. By focusing on enhancing the user experience and addressing any technological barriers, BCA can potentially improve customer engagement and increase actual usage of KlikBCA services. The study contributes to a deeper understanding of the factors driving digital banking adoption and provides valuable insights for banks looking to enhance their online service offerings. Future research could explore additional variables such as trust and security, which may also influence customer behavior in the context of online banking.